ANALISIS KONTRIBUSI PEREMPUAN DALAM PENGEMBANGAN PENDIDIKAN KARAKTER PADA NOVEL SI ANAK PEMBERANI - Faridatur Riskiyah; Eti Setiawati (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2022)
Women are often seen as an incapable group that does not have more capacity than men, but women are proven to have an important role in the development of character education. A novel as literature is a learning medium to introduce the essential role of women in character development amid the rise of contradictory reading materials containing harmful content contrasting with Pancasila values. This research aimed to examine the implicit values of character development in the novel